2000
DOI: 10.1590/s1020-49892000000600007
|View full text |Cite
|
Sign up to set email alerts
|

A prática anatômica e a formação médica

Abstract: A análise crítica das instituições de ensino médico revela o comprometimento de sua prática pedagó-gica com a instalação de um modelo de assistência distante e impessoal. Tal comprometimento se evidencia na adoção de uma metodologia de ensino que estimula o aluno a se destacar do seu objeto de trabalho e em uma noção de saber calcada nos crité-rios de cientificismo estabelecidos no século XVIII. A natureza, na modernidade, era vista como exterior ao homem e, portanto, como podendo ser objetivada. Ao cientista … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 11 publications
0
11
0
6
Order By: Relevance
“…Nonetheless, the student's confrontation with the cadaver in dissection triggers different emotional reactions, which over the last few decades have attracted the interest of several authors (Penney, 1985;Finkelstein and Mathers, 1990;Druce and Johnson, 1994), and which have been found to give rise to certain attitudes in relation to the death of future patients (Shalev and Natham, 1985) or even to affect the future doctorpatient relationship (Bastos and Proença, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the student's confrontation with the cadaver in dissection triggers different emotional reactions, which over the last few decades have attracted the interest of several authors (Penney, 1985;Finkelstein and Mathers, 1990;Druce and Johnson, 1994), and which have been found to give rise to certain attitudes in relation to the death of future patients (Shalev and Natham, 1985) or even to affect the future doctorpatient relationship (Bastos and Proença, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, some authors have investigated the emotional reactions of students faced with dissection (Cahill and Ettarh 2009;Hughes and Black 2006;Miguel-Pérez et al 2007;O'Carroll et al 2002;Perry and Ettarh 2009;Tschernig et al 2000) and the need for prior emotional preparation has been pointed out, considering that the student-cadaver relationship precedes and serves as a model for the future doctor-patient relationship (Arráez-Aybar et al 2008;Bastos and Proença 2000;Kostas et al 2007;Shalev and Nathan 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few decades, several authors have shown an interest in the reactions of medical students to dissection, especially their physical responses (Penney, 1985; Horne et al, 1990; Evans and Fitzgibbon, 1992; Druce and Johnsons, 1994), but also emotional ones (Harvill, 1986; Finkelstein and Mathers, 1990; Tschernig et al, 2000, Snelling et al, 2003; Arráez‐Aybar et al, 2004). Some even suggest that the first attitudes toward the cadaver could to some extent fashion the future doctor‐patient relationship (Shalev and Nathan, 1985; Bastos and Proença, 2000). Others have reported that seminars and courses have flourished when faculty try to incorporate humanistic values into an anatomy curriculum (Coulehan et al, 1995; Rizzolo, 2002; Stewart and Charon, 2002).…”
Section: Introductionmentioning
confidence: 99%